The artistic properties of the biographical method and interpretation of artistic psychology - Oripova Kamola Davlatovna (Genius Publishing Group, 2024)
This article is about the artistic properties of the biographical method and interpretation of artistic psychology. The works using the biographical method usually appear in three forms: the first - biographical studies based on the study of the creator's personality in the central place; the second - literary portrait works; the third is biographical novels and biographical stories based on the life of a certain creative person.
Keywords: Method; scientific-literary environment; biographical method; hero